Les passages de l'écriture - Bourneuf, Roland (Romanica Silesiana)
This comparative essay focuses on an ancient, multi-faceted process of rewriting, that the author tries to explore through his personal experience as a writer. Bourneuf begins with by writing about his scholarly research dealing with the influence of one author on another (especially the French-Canadian poet Saint-Denys Garneau) and proceeds to raise the question whether literature is indeed a continuous process of rewriting the same stories, characters, themes and myths. As a professor of literature and a writer, the author muses over the impact that French and foreign literatures had on his own literary career as the author of essays, short stories and novels. Key words: rewriting; comparatism; essay writing; story writing; myths